Effects of Elderly Gymnastics and Reflexology Program on Anxiety Among Elderly Using The Generalized Anxiety Disorder Screener (GAD-7) - Dwi Ratna Sari Handayani; Hafna Rosyita; Dewi Atika Putri; Imam Waluyo; Muhamad Arsyad Subu (International Journal of Social Service and Research, 2023)
The purpose of this study is to evaluate the impact of reflexology and elderly exercise as a combination intervention on lowering anxiety levels in seniors. The sample is a population that meets the inclusion criteria. The number of targeted samples is obtained using the average difference formula randomly. Number of respondents are 15 who fullfil the inclusion criteria aged 60-72 . The program package consists of reflexology combined with elderly exercises: Reflections are carried out: 2 times a week for 5 weeks, rlderly excersises is s is carried out 2 times a week. In measuring anxiety, the use the Generalized Anxiety Disorder Screener (GAD-7) has been proven to have high reliability and validity and identifies possible cases of generalized anxiety disorder and assesses the severity of symptoms. The respondents consist of 2 male (13.3%) and 13 female respondents (86.7%) with average age was 63.1 ± 2.2 and gender was differentiated into men with an average of 62.5 ± 3.5 then women with an average of 63.2 ± 2.1 then it is also known that the average level of anxiety before the intervention was 2.53 ± 3.52 with a 95% confidence level (95% CI) between 0.58 - 4.48 and the average level of anxiety after the intervention was 0.67 ± 1, 17 with a 95% confidence level (95% CI) between 0.02 – 1.30. into catagories 12 people (80%) had normal anxiety levels before the intervention, 2 people (13.3%) had mild, and 1 person (6.7%) had moderate and no severe. Wilcoxon test results, 7 respondents decreased anxiety levels, 3 respondents increased anxiety levels, and 5 respondents' anxiety remained the same as before undergoing the program package but statistically not significant Conclution: The resulth are obtained was 2,53 ± 3.52, and after the intervention, it was obtained 0,67 ± 1.17 for the level of anxiety using GADS by catagories measuring before and after was 6.43%. The level of mild and moderate anxiety after the intervention changed to 3.33%.